Antenatal Care &. Tetanus Toxoid Coverage in Pregnant Women in Semi-Urban Settings of Taluka Hala District Matiari - Jawaid Hussain Lighari, Atta Muhammad Chandio , (Journal of Peoples University of Medical & Health Sciences Nawabshah. (JPUMHS), 2015)
Objective: To assess and correlate the Antenatal care and Tetanus Toxoid vaccine coverage in Pregnant Women in Semi-Urban Settings ofTaluka Hala„ District Matiari. Study Design: Cross Sectional Study. Place & Duration: Department of Community Medicine PUMHS Nawabshah (SBA). Data was collected at semi-urban settings of Hala New District Matiari Sindh from August to September, 2014. Material & Methods: 320 women were selected by simple randomized sampling method of semi-urban setting of Hala New. The participants were questioned regarding their Antenatal seeking behavior of their last pregnancy and Tetanus Toxoid Vaccine. Data was analyzed by frequency tables, charts, 95% CI and Pearson correlation tests. Results: Study results show that 81.25% of women received antenatal care from a skilled health provider. Meanwhile 36.15% of women seek Antenatal Care from Lady Doctor, 33.85% by Lady Health Visitor & 30% by Midwives. 44.62% women have = four Antenatal Care visits in their last pregnancy. About g2.5% of women believe that ANC is essential for pregnancy. 74.37°A women have two doses of Tetanus Toxoid vaccination in their last pregnancy. 48.12% pregnant women delivered at Hospital, while 51.87% delivered at home. The study results show a significant correlation (association) between the number of ANC visits paid by women and education, occupational Status of women & her husband (p=0.001) and monthly Income/ Economical Status of the family (1)=0.004). Conclusion: The research study results conclude that with the passage of time ANC and Tetanus Toxoid Vaccination coverage has increased but current study is highlighting the need of universal coverage of ANC & T.T Vaccine. This would ensure the provision of basic health services to the women; it will ultimately help to achieve Millennium Development Goals (MDGs) 4 and 5. Considering this necessitate, there is also necessary to increase the literacy level and empowerment of women in country.